2014
DOI: 10.1039/c4sc01432d
|View full text |Cite
|
Sign up to set email alerts
|

Quinoidal diindenothienoacenes: synthesis and properties of new functional organic materials

Abstract: The synthesis and characterization of a series of quinoidal diindeno(thieno)thiophenes (DI[n]Ts) are reported. NIR absorption, deep LUMO energy levels and progressively tighter solid-state packing allude to organic materials applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 31 publications
0
58
0
1
Order By: Relevance
“…Despite the indenofluorene naming convention (i.e., an indene fused to a fluorene), analysis of the 1 H NMR spectrum, 16i NICS values and x-ray crystal structure data 16a, 16b of indeno[1,2- b ]fluorene ( 1 ) reveal that this compound is more accurately described as a benzo-fused para -xylylene derivative ( 1′ , Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the indenofluorene naming convention (i.e., an indene fused to a fluorene), analysis of the 1 H NMR spectrum, 16i NICS values and x-ray crystal structure data 16a, 16b of indeno[1,2- b ]fluorene ( 1 ) reveal that this compound is more accurately described as a benzo-fused para -xylylene derivative ( 1′ , Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Our initial report on the assembly of diones 10 and 11 utilized a Stille cross-coupling to construct key precursors 12 and 13 , respectively. 16l We have improved the preparation of diesters 12 and 13 by employing a Suzuki-Miyaura cross-coupling (Scheme 1), allowing us to selectively synthesize diones 10 or 11 on gram scale from commercially available starting materials without the use of column chromatography. Concurrent work on a separate project suggested that performing the final SnCl 2 -mediated reduction under rigorous anhydrous and anaerobic conditions could induce a significant increase in product yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Two common motifs for these molecules are extended polycyclic aromatic frameworks [4][5][6][7] and conjugated oligomers with terminal dicyanomethylene groups (e.g. QnTCN, Scheme 1).…”
mentioning
confidence: 99%
“…[15] We can dearomatize expanded central cores such as naphthalene (e.g., 11) [16] and thienoacenes (e.g., 12). [17] We have studied their redox chemistry [11] and photophysics [8] as well as made forays into materials applications. [13] Even the IF-diones are good electron acceptors; thus we have explored their optoelectronic properties [18] and solidstate packing.…”
mentioning
confidence: 99%